An assessment of emerging business models from blockchain technology - Serrano, Geraldo (University of the Philippines Diliman, Technology Management Center, 2017)
The emergence of the digital economy have disrupted and turned obsolete a number of traditional business models while giving birth to new business models attributed to it. Blockchain is one of the emerging digital technologies today that is expected to truly disrupt business models especially in industries that rely on trust, such as the financial sector. The public, shared, and tamper proof ledger are the core features of the technology and these allow people to transact with anyone on the network. This results in a "trustless economy" as the blockchain allows performing a transaction of any asset of value in a chronologically-updated, distributed, and cryptographically sealed manner while verification of the transactions happen with the consensus of system participants. With these core features of the technology, this research acknowledges that blockchain is capable of increasing transparency, enhancing efficiency, reducing risks, and cutting expenditures associated with transaction costs as evident in the first applications of the technology. Blockchain was introduced after the financial crisis in 2008 through a whitepaper that also introduced Bitcoin, the first blockchain technology and cryptocurrency. As evident, blockchain's first application is in the financial sector but with the other economic sectors that heavily relies on trust, blockchain is expected to be employed beyond its heavily financial use-cases. Smart contract is another application of blockchain that is expected to be employed by firms to change their current systems. Ethereum is an example of a blockchain technology platform with a smart contract functionality. The rise in popularity and adoption of the Bitcoin and Ethereum blockchains have resulted in the establishment of different blockchain startups patterned after their protocols while incumbent firms are pouring in millions of dollars in research and development (R&D) efforts to develop blockchains both privately and on a large scale. With the current hype about blockchain, the benefits as well as the drawbacks of the technology are surfacing.